Permeability characteristics of human endothelial monolayers seeded on different extracellular matrix proteins. Issue 5 (2000) - Nooteboom, Arjan; Hendriks, Thijs; Ottehöller, Irene; Van Der Linden, Cees. J.
Abstract : Objective: To investigate whether endothelial monolayer permeability changes induced by inflammatory mediators are affected by the extracellular matrix protein used for cell seeding. Methods: Human umbilical venular endothelial cells (HUVEC) were grown to confluent monolayers on membranes coated with either collagen, fibronectin or gelatin. The permeability to albumin and dextran was then assessed, both under normal conditions and after treatment with tumor necrosis factor-alpha (TNF-α) and bacterial lipopolysaccharide (LPS). Results: With any of the three protein coatings, tight junctions were formed all over the monolayers. The permeability of the coated membranes to albumin and dextran was reduced strongly by confluent monolayers; the relative reduction was similar for the three matrix proteins used. Pre-incubation of the monolayers with either TNF-α or LPS increased permeability dose dependently. However, the relative increase due to either treatment was independent of the protein used for membrane coating. Conclusion: The extracellular matrix protein used for initial seeding of endothelial cultures plays a minor role in determining the permeability changes induced in HUVEC monolayers by inflammatory mediators.